Free Migration between the EU and Switzerland: Impacts on the Swiss Economy and Implications for Monetary Policy - Peter Stalder (Swiss Journal of Economics and Statistics, 2010)
The agreement with the European Union on liberalized migration had sizable effects on the Swiss economy. Simulations with a macroeconometric model show that the agreement mitigated the incidence of labor shortages and stimulated business investment, giving rise to an increased growth potential. The inflow of new immigrants also affected the demand-side of the economy by boosting consumption and housing investment. As the supply-side effects prevailed, inflation was dampened. Monetary policy reacted by pursuing a more expansionary course. Annual GDP growth was raised by half a percentage point in the upswing 2004–2008. However, as the employment effect was of similar size, the widely expected productivity gains did not materialize. Moreover, the unemployment rate was lifted by 0.5 to 0.7 percentage points and household suffered from lower real wage growth. The consequences of the migration agreement over a full economic cycle are more difficult to assess. If the increased flexibility of labor supply observed in the recent upturn carries symmetrically over to recessions, the migration agreement reinforces the swings in GDP and employment growth but dampens the swings in unemployment and inflation. In contrast, if the reaction of migration flows to rising and falling labor demand is asymmetric, unemployment might increase over the cycle because recovering labor demand attracts additional foreigners while the formerly dismissed workers remain in the unemployment pool. These different possibilities are illustrated in the paper by additional model simulations.
Keywords: E24; J61; 330; unemployment; wages; business cycle; immigration